2005
DOI: 10.1093/deafed/eni002
|View full text |Cite
|
Sign up to set email alerts
|

Access to Postsecondary Education through Sign Language Interpreting

Abstract: Despite the importance of sign language interpreting for many deaf students, there is surprisingly little research concerning its effectiveness in the classroom. The limited research in this area is reviewed, and a new study is presented that included 23 interpreters, 105 deaf students, and 22 hearing students. Students saw two interpreted university-level lectures, each preceded by a test of prior content knowledge and followed by a post-lecture assessment of learning. A variety of demographic and qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 10 publications
7
42
2
1
Order By: Relevance
“…The results indicates lack of statistical significant differences due to the effectiveness of the interpreter academic qualification in all aspects except for the professional aspect differences attributable to the diploma where this finding is consistent with the result with the study conducted by (Marschark et al, 2005) entitled "Access to education beyond high school through sign language interpretation" as the goal of this study is to identify the effectiveness of sign language interpreters for the deaf in the classroom, the study concluded that there were discrepancies regarding the importance of the students prefer the interpretation, and pointed out that deaf students gain less information from their fellow listeners, as they are weak in their school homework, the quality of education and the quality of interpretation as well.…”
Section: Discussion Of the Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…The results indicates lack of statistical significant differences due to the effectiveness of the interpreter academic qualification in all aspects except for the professional aspect differences attributable to the diploma where this finding is consistent with the result with the study conducted by (Marschark et al, 2005) entitled "Access to education beyond high school through sign language interpretation" as the goal of this study is to identify the effectiveness of sign language interpreters for the deaf in the classroom, the study concluded that there were discrepancies regarding the importance of the students prefer the interpretation, and pointed out that deaf students gain less information from their fellow listeners, as they are weak in their school homework, the quality of education and the quality of interpretation as well.…”
Section: Discussion Of the Findingssupporting
confidence: 91%
“…A study conducted by Marschark et al (2005) entitled "Access to education beyond high school through sign language translation", and the goal of this study was to identify the effectiveness of sign language interpreters for the deaf in the classrooms, the sample consisted of 150 people, including (127) student volunteers from the Institute of Technology for the deaf rooster, among these volunteers (22) ordinary students, including (9) males and the rest were females, (105) deaf students, including 60 males and females as well as the rest (23) sign language interpreter. The researcher assigned interpreters during lectures for deaf students at the university level, then all students set for a test to see how to take advantage of the content and understanding it, where the results indicated that there were discrepancies regarding the students preferring of having interprets, and the results also pointed out that deaf students gain less information than their listening colleague, as they are weak in school readiness, quality of education and interpretation.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…For Marschark et al (2005), one of the assumptions of inclusion is that the discursive structure and information transmitted by a hearing professor to hearing students is appropriate to the knowledge and learning styles of deaf students. But deaf students form a more heterogeneous group than those who can hear.…”
Section: Young Deaf People In the University Contextmentioning
confidence: 99%
“…Sign Language interpreters have been traditionally used during the class for deaf students' inclusion. However, nowadays not every student with hearing disability uses Sign Language, thus signing does not provide deaf students full access to classroom information [1]. Nowadays, some researchers are working in lectures transcription based on Automatic Speech Recognition (ASR).…”
Section: Introductionmentioning
confidence: 99%